Regulatory Role of OsMADS34 in the Determination of Glumes Fate, Grain Yield, and Quality in Rice - Ren, Deyong; Rao, Yuchun; Leng, Yujia; Li, Zizhuang; Xu, Qiankun; Wu, Liwen; Qiu, Zhennan; Xue, Dawei; Zeng, Dali; Hu, Jiang; Zhang, Guangheng; Zhu, Li; et al. (Frontiers in Plant Science, 2016)
Grasses produce seeds on spikelets, a unique type of inflorescence. Despite the importance of grass crops for food, the genetic mechanisms that control spikelet development remain poorly understood. In this study, we used m34-z, a new mutant allele of the rice (Oryza sativa) E-class gene OsMADS34, to examine OsMADS34 function in determining the identities of glumes (rudimentary glume and sterile lemma) and grain size. In the m34-z mutant, both the rudimentary glume and sterile lemma were homeotically converted to the lemma-like organs and acquired the lemma identity, suggesting that OsMADS34 plays important roles in the development of glumes. In the m34-z mutant, most of the grains from the secondary panicle branches were decreased in size, compared with grains from wild type, but no differences were observed in the grains from the primary panicle branches. The amylose content and gel consistency, and a seed-setting rate from the secondary panicle branches were reduced in the m34-z mutant. Interesting, transcriptional activity analysis revealed that OsMADS34 protein was a transcription repressor and it may influence grain yield by suppressing the expressions of BG1, GW8, GW2 and GL7 in the m34-z mutant. These findings revealed that OsMADS34 largely affects grain yield by affecting the size of grains from the secondary branches.